Corporate Governance and Board Conflict Management - Segun Kehinde; Chinonye Moses; Taiye Borishade; Oladele Kehinde; Simon Ilogho; Kemi Kehinde (MultiTech Publisher, 2023)
In managing board conflicts, which result from the conflicting interests and preferences of directors, shareholders, and other stakeholders, this essay examines the function of corporate governance. We examine the theoretical and empirical research on the causes, nature, and effects of board conflicts, as well as the methods for preventing, resolving, or reducing them. We also note some gaps and difficulties that need to be addressed in this area's ongoing research. We contend that for board members and stakeholders to work effectively, there must be a balance between alignment and diversity, contestation and collaboration, and harmony an md disruption.